2013
DOI: 10.1104/pp.113.224378
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Bacterial-Like Phosphoprotein Phosphatases in Photosynthetic Eukaryotes Features Ancestral Mitochondrial or Archaeal Origin and Possible Lateral Gene Transfer      

Abstract: Protein phosphorylation is a reversible regulatory process catalyzed by the opposing reactions of protein kinases and phosphatases, which are central to the proper functioning of the cell. Dysfunction of members in either the protein kinase or phosphatase family can have wide-ranging deleterious effects in both metazoans and plants alike. Previously, three bacterial-like phosphoprotein phosphatase classes were uncovered in eukaryotes and named according to the bacterial sequences with which they have the great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 73 publications
5
55
0
Order By: Relevance
“…In humans and Arabidopsis (Arabidopsis thaliana) the canonical eukaryotic PPP Ser/Thr protein phosphatase complement is encoded by 13 and 26 catalytic subunits respectively, most of which require interaction with regulatory proteins to direct their specificity within the cell (Moorhead et al, 2009;Heroes et al, 2013;Uhrig et al, 2013b). In Arabidopsis and all other plants, we have uncovered a unique subfamily of prokaryotic-like PPP-family phosphatases called the Shewanella-like protein (SLP) phosphatases (Andreeva and Kutuzov, 2004;Uhrig and Moorhead, 2011;Uhrig et al, 2013a), which was found to further divide into two distinct groups called SLP1 and SLP2, differing in both subcellular localization and spatial expression across the plant (Uhrig and Moorhead, 2011). Characterization of SLP phosphatases from Arabidopsis (At) showed that AtSLP1 is chloroplast targeted and expressed exclusively in photosynthetic tissues, while AtSLP2 is likely cytosolic and highly expressed in nonphotosynthetic tissues (Uhrig and Moorhead, 2011).…”
mentioning
confidence: 99%
“…In humans and Arabidopsis (Arabidopsis thaliana) the canonical eukaryotic PPP Ser/Thr protein phosphatase complement is encoded by 13 and 26 catalytic subunits respectively, most of which require interaction with regulatory proteins to direct their specificity within the cell (Moorhead et al, 2009;Heroes et al, 2013;Uhrig et al, 2013b). In Arabidopsis and all other plants, we have uncovered a unique subfamily of prokaryotic-like PPP-family phosphatases called the Shewanella-like protein (SLP) phosphatases (Andreeva and Kutuzov, 2004;Uhrig and Moorhead, 2011;Uhrig et al, 2013a), which was found to further divide into two distinct groups called SLP1 and SLP2, differing in both subcellular localization and spatial expression across the plant (Uhrig and Moorhead, 2011). Characterization of SLP phosphatases from Arabidopsis (At) showed that AtSLP1 is chloroplast targeted and expressed exclusively in photosynthetic tissues, while AtSLP2 is likely cytosolic and highly expressed in nonphotosynthetic tissues (Uhrig and Moorhead, 2011).…”
mentioning
confidence: 99%
“…[1][2][3] The Arabidopsis PP2A regulatory subunits (B subunits) are classified into 3 non-related families; B/B55 (a and b), B' (a, b, g, d, e, z, h, u, and k), and B" (a, b, g, d, e, and TON2). 4,5 The B' family is divided into 3 subfamilies a, h, and k, where the h subfamily comprises the close homologs B'h, B'g, B'u, and B'z.…”
mentioning
confidence: 99%
“…The PPP superfamily contains conserved four-sequence motifs, GDXHG, GDXXDRG, GNHE and HGG, where X is any residue in the N-terminal subdomain of about 100 amino acids [8,17]. M. xanthus PrpA contains the three core signature motifs (GDXHG, GDXXDRG, and GNHE); however, M. xanthus ApaH possesses modified motifs 2 and 3, i.e., GDXXAKG and GNHD sequences, …”
Section: Comparison Of the Amino Acid Sequences Of Prpa And Apahmentioning
confidence: 99%
“…One group of bacterial PPPs shares homology with diadenosine tetraphosphate (Ap 4 A) hydrolases (ApaHs), and is termed ApaHlike phosphatases [7][8][9]. The Ap 4 A is composed of two adenosine moieties joined in a 5-5 0 linkage by a chain of four phosphates that is ubiquitous in prokaryotic and eukaryotic cells [10].…”
Section: Introductionmentioning
confidence: 99%